(untitled) (Academia Science Repository, 2023)
The Covid-19 pandemic has had a great impact on the development of world politics and economy. The world economy and national economies have faced enormous difficulties due to the new type of coronavirus pandemic. The social sphere, the health care system has experienced difficult times and is still forced to face the consequences caused by this disease. The pandemic has covered all important aspects of life, from human health to the social sphere. Biohazards were not seen as a priority threat by politicians and policy experts prior to the crisis. But it soon became clear that the coronavirus crisis poses an equal threat not only to human life, but also to the global world order.